Psychological Distress, Somatic Complaints, and Their Relation to Negative Psychosocial Factors in a Sample of Swedish High School Students - Kerekes, Nóra; Zouini, Btissame; Tingberg, Sofia; Erlandsson, Soly (Frontiers in Public Health, 2021)
Background Adolescence is a period in life characterized by major neurobiological, physiological, and psychological changes. Those changes may give rise to worsened mental health and an increased prevalence of somatic complaints combined with a negative psychosocial environment. Rapid changes in society, which may also affect young people in several ways, call for a renewed screening of today's adolescents' mental and somatic well-being. Aim The present study's primary aim was to measure the level of self-rated psychological distress and the prevalence of somatic complaints in a sample of Swedish high school students. As a secondary aim, it identifies gender-specific patterns and examines mental and somatic health in relation to negative psychosocial factors (such as parental alcohol use problems or the experience of physical or psychological abuse). Method 287 Swedish high school students completed a survey including the Brief Symptom Inventory (BSI) and a questionnaire about the presence of defined somatic complaints. In order to examine the relationship between negative psychosocial factors and mental and somatic health, three groups were formed: those reporting (i.) parental substance use problems, (ii.) previous experience of abuse, (iii.) none of these problems. Results The majority of the Swedish high-school students (> 80%) reported no or only a few problems with psychological distress and no or only one somatic complaint. Female students disclosed a significantly higher psychological distress level captured by each BSI domain. The number of somatic complaints was similarly distributed between the genders. The students rarely reported parental substance use problems, but almost 40% of the male and 50% of the female students indicated the experience of physical and/or psychological abuse. Such negative psychosocial circumstances were related to an increased level of anxiety in the male and an increased general level of psychological distress in female students. Conclusions The study confirmed female students’ higher psychological distress level. Gender differences in the type of physical complaints, but not number were detected. The experience of physical and/or psychological abuse was found to significantly worsen psychological distress in students of both genders.